2012
DOI: 10.1371/journal.pone.0052199
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and In Vitro and In Vivo Biological Studies of a 3′-Deoxythymidine Conjugate that Potentially Kills Cancer Cells Selectively

Abstract: Thymidine kinases (TKs) have been considered one of the potential targets for anticancer therapeutic because of their elevated expressions in cancer cells. However, nucleobase analogs targeting TKs have shown poor selective cytotoxicity in cancer cells despite effective antiviral activity. 3′-Deoxythymidine phenylquinoxaline conjugate (dT-QX) was designed as a novel nucleobase analog to target TKs in cancer cells and block cell replication via conjugated DNA intercalating quinoxaline moiety. In vitro cell scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Cells were plated overnight at 5,000 per well on a 96-well plate and then treated with 50 μM dT-QX for 24 h in the growth media containing 10% serum and 0.1% DMSO. MTT assay was carried out as reported [ 29 ], and cell viability was plotted using GraphPad Prism software (GraphPad Software, USA). Thymidine analog dT-QX was synthesized as previously reported [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were plated overnight at 5,000 per well on a 96-well plate and then treated with 50 μM dT-QX for 24 h in the growth media containing 10% serum and 0.1% DMSO. MTT assay was carried out as reported [ 29 ], and cell viability was plotted using GraphPad Prism software (GraphPad Software, USA). Thymidine analog dT-QX was synthesized as previously reported [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a different selective cytotoxic thymidine analog would be needed. Recently, we reported a thymidine quinoxaline conjugate (dT-QX) with a broad spectrum of anticancer activity and low cytotoxicity on the normal liver cell line [ 29 ]. Although the selectivity of dT-QX was attributed to its unique thymidine linked chemical structure (Figure 1 a), the molecular pathways responsible for the selectivity are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mice were euthanized after 6 days and H22 cells were harvested with PBS solution. H22 cells were washed once with sterile PBS and were injected subcutaneously (3×10 6 cells per mouse) at the lower back of nude BALB/c mice [31]. Typically, tumors reached an average size of 0.8×0.6 cm after 7 days post injection, and mice were used in the following imaging analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The synthesis, in vitro and in vivo biological activities of 39‐deoxythymidine phenylquinoxaline (dT‐QX, 29 ) have been reported (Figure ) . This bioconjugate was synthesized by the Huisgen azide–alkyne cycloaddition reaction.…”
Section: Nucleoside and Nucleotide Bioconjugates In Cancer Therapymentioning
confidence: 99%
“…The anticancer activity of dT‐QX ( 29 ) was attributed to its selective inhibition of DNA synthesis, resulting in extensive mitochondrial superoxide stress in cancer cells. Preliminary in vivo studies within a subcutaneous liver tumor xenograft model showed that dT‐QX inhibits the growth of tumors with EC 50 values in the range of 6.6–42 μ m . The scope of the nucleoside bioconjugates has been elaborated by the incorporation of the Cinchona alkaloids ( 30 ), which were used as fluorescent markers and exhibited in vitro cytotoxicity in human KB (nasopharynx carcinoma) tumor tissue culture …”
Section: Nucleoside and Nucleotide Bioconjugates In Cancer Therapymentioning
confidence: 99%